Design Of Switched Reluctance Motor Using Finite Element Method - Abdullah, Nurfaezah; Abdul Karim, Kasrul; Raja Othman, Raja Nor Firdaus Kashfi; Mohd Jamil, Mohd Luqman; Othman, Md Nazri (Publications International, 2014)
This paper presents a design of switched reluctance motor (SRM) for electric scooter using an empirical method. A common experience designer usually designs an electric motor by analytical or magnetic field analysis. It provides difficulties for those who have lacks of experience on designing reluctance motor. So this paper aim to produce a guidelines to construct a switched reluctance motor. In this paper switched reluctance motor is modelled using an empirical method and established for a quick references by selecting geometry of SRM in other previous literature. Later, the designed model is analyzed using ANSYS Maxwell finite elements software. The initial SRM design has been developed and analyzed using RMxprt tools for preliminary parameter. Next, the model will be tesedt using Maxwell two dimensional with standard external circuit excitation to expect the output performance The same model in Maxwell two dimensional has been excited with phase voltage excitation sequences to achieve less torque ripple. The expectation from this simulation is to determine the speed torque profile by using two method as above mentiond. Anticipation from the modeling, the output speed torque profile is achieved .